Implementation of Block System Learning in Al Hikmah Penajam Integrated Islamic High School - Fadhilah Mujahidah; Zahruddin; Maftuhah (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2022)
This study aims to describe the learning activities at Al Hikmah Penajam Integrated Islamic High School, which implements a block learning system. The block system is a process of student interaction with the teacher and learning resources by grouping material, grouping time, and implementing schedules. The research method used is descriptive qualitative with sources from school principals, teachers, and students. In addition, researchers also made direct observations to gather data related to block system learning which was carried out at SMA IT Al Hikmah and studied data documentation related to information on the implementation of the learning block system. The data analysis technique is interactive data analysis, data reduction, data presentation, and verification. The results of this study indicate that learning using the 2013 curriculum with the implementation of this block learning system is 2 to 3 meetings (1 meeting consisting of 4 hours of lessons x 45 minutes) combined into one session with 8 to 12 hours of lessons x 45 minutes a week. This calculation is based on the accumulated hours per syllabus. Obstacles in implementing learning are the application of blocks, conditions for students, sources of teacher background, and student learning media, including books, wi-fi, and LCDs.